Matrix metalloproteinase-2 and its correlation with basal membrane components laminin-5 and collagen type IV in paediatric burn patients measured with Surface Plasmon Resonance Imaging (SPRI) biosensors. Issue 4 (June 2018) - Weremijewicz, Artur; Matuszczak, Ewa; Sankiewicz, Anna; Tylicka, Marzena; Komarowska, Marta; Tokarzewicz, Anna; Debek, Wojciech; Gorodkiewicz, Ewa; Hermanowicz, Adam
Highlights: MMP-2, laminin-5 and collagen type IV plasma levels were elevated early after thermal injury. MMP-2, laminin-5 and collagen type IV plasma levels were highest 2–16 h after burn. Abstract: The purpose of this study was the determination of matrix metalloproteinase-2 and its correlation with basal membrane components laminin-5 and collagen type IV in the blood plasma of burn patients measured with Surface Plasmon Resonance Imaging (SPRI) biosensors. Material and methods: 31 children scalded by hot water who were managed at the Department of Paediatric Surgery between 2014–2015, after primarily presenting with burns in 4–20% TBSA were included into the study (age 9 months up to 14 years, mean age 2, 5 + 1 years). There were 10 girls and 21 boys. Venous blood samples were drawn 2–6 h, and 12–16 h after the thermal injury, and on the subsequent days 3, 5 and 7. The matrix metalloproteinase-2, collagen type IV and laminin-5 concentrations were assessed using Surface Plasmon Resonance Imaging by the investigators blinded to the other data. Results: The MMP-2, laminin-5 and collagen type IV concentrations in the blood plasma of patients with burns, were highest 12–16 h after thermal injury, the difference was statistically significant. The MMP-2, laminin-5 and collagen type IV concentrations measured 3 days, 5 days and 7 days after the thermal injury, slowly decreased over time, and on the 7th day reached the normal range, when compared with the concentration measured in controls. Conclusion: Current work is the first follow-up study regarding MMP-2 in burns. MMP-2, laminin-5 and collagen type IV levels were elevated early after burn injury in the plasma of studied patients, and were highest 12–16 h after the injury. MMP-2, laminin-5 and collagen type IV levels were not proportional to the severity of the burn. We believe in the possibility that the gradual decrease of MMP-2, collagen type IV and laminin-5 concentrations could be connected with the process of healing, but to prove it, more investigation is needed in this area. The SPR imaging biosensor is a good diagnostic tool for determination of MMP-2, laminin-5 and collagen type IV in blood plasma of patients with burns.